Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/09585192.2017.1396545
|View full text |Cite
|
Sign up to set email alerts
|

The role of the psychological contract in shaping graduate experiences: a study of public sector talent management programmes in the UK and Australia

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints-eprint.ncl.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 95 publications
(87 reference statements)
1
29
0
4
Order By: Relevance
“…According to the evidence, supervisors and leaders can play a significant role in shaping the attitude of talented employees towards organisations' talent management strategies (Bratton, 2018;King, 2016). Similarly, Clarke and Scurry (2017) found that line managers play a crucial role in continuous development and fulfilment of graduate trainees' psychological contract in talent management programme. Also, CEO/owner-managers' commitments are essential for effective implementation of talent management strategies through the creation of talent mindset/culture at all levels within the organisation (Sheehan et al, 2018).…”
Section: Methodological Assessmentmentioning
confidence: 94%
See 3 more Smart Citations
“…According to the evidence, supervisors and leaders can play a significant role in shaping the attitude of talented employees towards organisations' talent management strategies (Bratton, 2018;King, 2016). Similarly, Clarke and Scurry (2017) found that line managers play a crucial role in continuous development and fulfilment of graduate trainees' psychological contract in talent management programme. Also, CEO/owner-managers' commitments are essential for effective implementation of talent management strategies through the creation of talent mindset/culture at all levels within the organisation (Sheehan et al, 2018).…”
Section: Methodological Assessmentmentioning
confidence: 94%
“…King, 2016), psychological contracts fulfilment (e.g. Clarke and Scurry, 2017;King, 2016;Sonnenberg et al, 2014), perceived fairness in talent management and career outcomes (e.g. King, 2017), employee value proposition (e.g.…”
Section: Methodological Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Organizations often struggle with their TM efforts, sometimes explained by the existence of a war for talent (Michaels et al, 2001), in which one important issue is the shortage of qualified workers (Latukha, 2015). This issue is especially prevalent in public sector organizations, where a chronic shortage of talented people has been observed (Clarke and Scurry, 2017;Glenn, 2012). Furthermore, TM challenges are distinctive in Sweden, a country which overtook the USA in 2016 in terms of being most in need of skilled workers (Hay Group, 2016).…”
Section: Introductionmentioning
confidence: 99%